Prevalensi Kasus Demam Tifoid di Puskesmas Kampili Kabupaten Gowa - Mus, Rosdiana; Sulfiani, Sulfiani; Abbas, Mutmainnah; Asni, Asni; Asmin, Elpira; Tamalsir, Dylan; Agustina, Titin (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Typhoid fever is caused by Salmonella typhi bacteria which attacks the digestive tract. Typhoid fever is transmitted through contaminated food or drink. The aim of this research was to see the prevalence of typhoid fever and the average results of widal at Kampili health center. The research method was descriptive observation based on medical record data from January 2019-August 2020 at the Kampili Public Health Center. The results obtained 251 data on typhoid fever patients with a prevalence of 1.7%. Based on the highest month of visit in January and February 2019, 25 patients (9.96%) respectively, the lowest month was June, July and August 2020, which was 1 patient (0.39%) each, prevalence based on male 112 (44.6%) and female 139 (55.4%). Based on the highest age group at the age of 5-20 years 135 (53.8%). The results of widal examination were found to be mostly in O 1/320 reagent as much as 202 (80.4%), H 1/320 reagent as much as 91 (36.3%). AH reagent had the most negative results, 89 (35.5%) and BH reagent 1/80 as much as 106 (42.2%) and the results of widal examination in male were mostly O 1/320 reagent as much as 85 (75.9%), H  reagent 1/320 45 (40.2%). In female, the highest of O 1/320 reagent was 117 (84.2%), H  reagent 1/160 was 49 (35,3%) age 5-20 years. The prevalence rate of typhoid fever is still high and laboratory supporting examinations other than Widal titer can be carried out to support the diagnosis of typhoid fever. Keywords: Typhoid, Prevalence, Salmonella  ABSTRAK Demam tifoid disebabkan bakteri Salmonella typhi yang menyerang saluran pencernaan. Penularan demam tifoid melalui  makanan atau minuman yang terkontaminasi. Tujuan penelitian untuk melihat  prevalensi demam tifoid dan rata-rata hasil widal di Puskesmas Kampili.  Metode penelitian adalah Deskriptif Observasi berdasarkan data Rekam Medis Januari 2019-Agustus 2020 di Puskesmas Kampili. Hasil Penelitian didapatkan 251 data pasien demam tifoid dengan prevalensi 1,7%. Berdasarkan bulan kunjungan tertinggi pada Januari dan Februari 2019 yang masing-masing 25 pasien (9,96%), bulan terendah pada Juni, Juli dan Agustus 2020 yang masing-masing 1 pasien (0,39%). Prevalensi berdasarkan jenis kelamin laki-laki 112 (44,6%) dan perempuan 139 (55,4%) dengan kelompok usia 5-20 tahun 135 (53,8%). Hasil Pemeriksaan widal pada reagen O 1/320 sebanyak 202 (80,4%), reagen H 1/320 sebanyak 91 (36,3%), reagen AH terbanyak hasil negatif yaitu 89 (35,5%) dan reagen BH 1/80 sebanyak 106 (42,2%). Hasil pemeriksaan widal pada laki-laki terbanyak reagen O 1/320 sebanyak 85 (75,9%), reagen H  1/320 45 (40,2%) dan perempuan terbanyak reagen O 1/320 sebanyak 117 (84,2%), reagen H 1/160 sebanyak 49 (35.3%). Kesimpulan menunjukkan prevalensi demam tifoid di puskesmas Kampili lebih banyak terjadi pada perempuan di bandingkan dengan laki-laki dengan usia 5-20 tahun. Angka prevalensi kejadian demam tifoid yang masih tinggi dan pemeriksaan penunjang laboratorium selain titer widal dapat dilakukan untuk menunjang diagnosis demam tifoid. Kata Kunci: Demam Tifoid, Prevalensi, Salmonella